What goes up must come down: A tripartite Dok‐3/Grb2/SHIP1 inhibitory module limits BCR signaling. Issue 11 (3rd November 2016) - Reth, Michael; Gold, Michael R.
Abstract : Manno et al . show that the B‐cell receptor (BCR) can directly recruit inositol 5'‐phosphatase (SHIP1), a lipid phosphatase that dephosphorylates phosphatidylinositol 3, 4, 5‐trisphosphate (PIP3 ) and prevents excessive B cell activation. Binding of the Dok‐3 and Grb2 adaptor proteins to SHIP1 stabilizes its interaction with the BCR at the plasma membrane. Abstract : Properly regulated immunity requires precise integration of activating and inhibitory signals. As for other lymphocytes, B cells express an antigen‐specific activating receptor, the B‐cell antigen receptor (BCR), and inhibitory receptors (e.g. FcγRIIb) that exercise checkpoint control on B‐cell activation. Moreover, following BCR engagement, CD19 recruits proteins that amplify BCR signaling, while CD22 initiates a negative feedback loop by recruiting proteins that inhibit BCR signaling. Initial BCR signaling is mediated by protein tyrosine kinases and lipid kinases; inhibitory receptors directly antagonize the actions of these enzymes by recruiting protein tyrosine phosphatases and lipid phosphatases and positioning them close to actively signaling BCRs. Previously it was thought that inhibitory receptors such as FcγRIIb and CD22 were essential for bringing these phosphatases near the BCR. In this issue of the European Journal of Immunology, Manno et al. show that a tripartite inhibitory module consisting of the adaptor proteins Dok‐3 and Grb2 and the lipid phosphatase SHIP1 binds directly to activated BCRs and limits the Ca 2+ mobilization that is required for B lymphocyte activation. This reveals that the BCR can be both an activating and inhibitory receptor, one that activates signaling enzymes while initiating a negative feedback loop that prevents excessive signaling.